(untitled) (Journal of the College of Basic Education, 2023)
The current research is to identify the cognitive distortions of public and private kindergarten teachers, and the current research is limited to kindergarten teachers in the third Baghdad / Rusafa governorate for the academic year 2018/2019. The researcher chose a sample of her research from the kindergarten teachers belonging to the third directorate of education / Al-Rusafa, numbering (50) female teachers, in a simple random way, with a number of (30) female teachers from the government kindergarten in (3) kindergartens and (20) female teachers from private kindergartens in (3) Private Kindergarten. The researcher adopted the (Thuwaini 2018) scale. This scale consists of (50 paragraphs) and in front of each paragraph three alternatives to the answer are (always, often, sometimes) so that a score of 3 for the alternative was always given and a score of 2 for the alternative is often given and a degree 1 for the alternative sometimes and thus the highest degree gets The parameter on the scale is 150 degrees and the lowest degree is 50, so the hypothetical mean of the scale becomes 75. In order to verify the apparent honesty, the researcher presented her research tool to a group of experts and specialists in the field of educational and psychological sciences. The researcher approved the calculation of the stability of the current scale, which is the method of thought and the climate of the stability factor calculated in this way (0.81), which is a good stability factor, and the researcher concluded that the kindergarten teachers Governmental and private are not characterized by cognitive distortions.